Rancang Bangun Mesin Penetas Telur Burung Love Bird Otomatis Berbasis Arduino Uno R3 - Hartayu, Ratna; Santoso, Santoso (Program Studi Teknik Elektro S1 ITN Malang, 2023)
Caring for birds is in great demand among bird lovers both in terms of maintenance and maintenance which is quite easy, just pay attention to diet and cleanliness of the place. Birds that enter the adult mass will experience overheat, which is a sign that they are ready to be bred and ready to breed. However, problems arise when the bird does not want to incubate its eggs due to certain factors. A fully automatic bird egg incubator using Arduino UNO is needed, which is a tool that functions to incubate bird eggs automatically and perfectly without having to be incubated by the parent, with the aim of reduce the failure rate in raising birds and increase the process of hatching the eggs. This machine regulates the temperature and humidity levels as well as egg rotation so that the resulting temperature can be evenly distributed automatically without having to touch the eggs during the hatching process as a substitute for the natural incubation process by the mother. The temperature needed to incubate the eggs ranges from 37.5°C to 40°C and humidity ranges from 35% to 60%.